Plan exportador de aperitivo vinico de café de la empresa licorera española hacia Estados Unidos (2013)
Licorera Española of the city of Armenia Quindío, is a producer and marketer of coffee drinks that offers products of excellent quality. Currently it distributes in the national market in cities like Dosquebradas, Manizales, Medellín, Salento, Bogota, Popayán, Neiva, Villavicencio and Ibagué; which means that its positioning process in the domestic market is well advanced. Considering the coffee strength of the Quindiana region and therefore of Colombia, in addition, considering the worldwide recognition of Colombian coffee, it is presumed the attraction to this product by international consumers, for that reason arises the idea of ​​carrying out a research work about the feasibility of exporting a Coffee Snack to the international market. Since this Appetizer has characteristics that stand out as it corresponds to its smell, taste and texture; making this a competitive and interesting product to the international market.